2002
DOI: 10.1046/j.1439-0450.2002.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Outbreak of Malignant Catarrhal Fever in a Beef Herd in Israel

Abstract: Malignant catarrhal fever (MCF. corrizza contagiosa) is an invariably fatal communicable disease in cattle, whose causative agent is the ovine herpes virus-2, or the alcelaphine herpes virus-1. In one feed-lot family farm, 34 calves out of 100 became ill at the rate of one to four calves per week, and all of them subsequently died over a period of 4 months. Most of the initial cases were manifested clinically as the head and eye form, but most of the entire clinical spectrum of forms (the respiratory, intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 7 publications
3
37
2
7
Order By: Relevance
“…Thus, this research provides The seroprevalence of OvHV-2 infection reported in the present study (37.66%) was lower when compared to that of the previous study conducted in Japan (64.3%) [22]. In the U.S.A., OvHV-2 was associated with 53 to 59% of serologically positive sheep [12], while seropositivity in Germany was reported prevalence as 75% [7], and that of the Middle East, which was greater than 70 to 95% [5]. In addition, species that may harbor MCF viruses, including sheep and goats, have a higher frequency of seropositivity (>90%) than do MCF-susceptible species including cattle, bison, deer, caribou, elk (Cervus elaphus) and moose, which ranges from a few percent to 50% seropositive [7,12,21], indicating their status as silent carriers of the MCF virus.…”
Section: Malignant Catarrhal Fever (Mcf) Is An Infectious Disease Of contrasting
confidence: 61%
See 1 more Smart Citation
“…Thus, this research provides The seroprevalence of OvHV-2 infection reported in the present study (37.66%) was lower when compared to that of the previous study conducted in Japan (64.3%) [22]. In the U.S.A., OvHV-2 was associated with 53 to 59% of serologically positive sheep [12], while seropositivity in Germany was reported prevalence as 75% [7], and that of the Middle East, which was greater than 70 to 95% [5]. In addition, species that may harbor MCF viruses, including sheep and goats, have a higher frequency of seropositivity (>90%) than do MCF-susceptible species including cattle, bison, deer, caribou, elk (Cervus elaphus) and moose, which ranges from a few percent to 50% seropositive [7,12,21], indicating their status as silent carriers of the MCF virus.…”
Section: Malignant Catarrhal Fever (Mcf) Is An Infectious Disease Of contrasting
confidence: 61%
“…The lower prevalence reported in this study might be due to use of the SN test, which is different from the tests used in other studies. For example, the complement fixation test was used in the previous study conducted in Japan [22], an enzyme-linked immunosorbent assay was used to detect OvHV-2 antibodies in the studies performed in the U.S.A. and Germany [7,12], and PCR was used to detect OvHV-2 antibodies in a study performed in Israel [5]. Ideally, a comparison with other tests would increase information about the reliability of the infection rate obtained using the SN assay, but this was outside the scope of this study.…”
Section: Malignant Catarrhal Fever (Mcf) Is An Infectious Disease Of mentioning
confidence: 99%
“…ALBINI et al 2003, BARNARD et al 1994, BRENNER et al 2002, CLARK et al 1970, COLLERY u. FOLEY 1996, DECARO et al 2003, DRIEMEIER et al 2002, FRITZ et al 1992, FRÖLICH et al 1998, GULLAND et al 1989, HÄNICHEN et al 1998, HATKIN 1980, KALUNDA et al 1981, KIUPEL et al 2004, LI et al 2006, LØKEN et al 1998, MACKINTOSH 1992, MÜLLER-DOBLIES et al 2001, SYRJÄLÄ et al 2006, WANI et al 2006, WIYONO et al 1994, ZARNKE et al 2002 Problemstellung der hier vorliegenden Arbeit:…”
Section: Abbildung 1: Weltweite Verbreitung Von Bkfunclassified
“…Meist erkranken nur einzelne Tiere einer Herde. Dennoch gibt es bei allen Tierarten immer wieder Berichte, bei denen die gesamte Herde erkrankte (BEDELIAN et al 2007;BRENNER et al 2002;BROWN und BLOSS 1992;HÄNICHEN et al 1998;HATKIN 1980;LI et al 2006a;ORR et al 1988;TOMKINS et al 1997). …”
Section: Klinikunclassified
“…As to its epidemiology, many reports have described this virus's worldwide distribution, but so far its disease status has not been completely documented in Brazil (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%